Modeling Aboveground Biomass and Stand Density Using Forest Canopy Density in a Tropical Natural Forest Concession - Reza Dwiputra Perdhana; Lilik Budi Prasetyo; Rachmad Hermawan (Postgraduate, University of Mataram, 2026)
Natural forests within the concession area of PT Bharinto Ekatama are critical for carbon storage and ecosystem service provision, yet efficient methods to quantify stand biophysical parameters at scale remain limited. This study developed spatial models to estimate stand density and aboveground biomass using the Forest Canopy Density (FCD) approach. Field data were collected from 30 plots (50 × 50 m) between January and June 2025, complemented by Landsat 8 OLI/TIRS imagery. FCD was derived from the integration of Advanced Vegetation, Bare Soil, Shadow, and Thermal indices. Relationships between FCD and field-based measurements were evaluated using linear regression. The forest community comprised 47 species across 21 families, dominated by Dipterocarpus. FCD values ranged from 49.05% to 85.22%, while aboveground biomass and stand density ranged from 37.36–331.65 ton ha⁻¹ and 660–2,224 trees ha⁻¹, respectively. The models demonstrated strong explanatory power (R² = 0.8335 for stand density; R² = 0.8317 for biomass; p < 0.05). Validation yielded RMSE values of 151.662 trees ha⁻¹ and 29.695 ton ha⁻¹, corresponding to normalized errors of 12% and 22%. These findings indicate that the FCD approach provides a robust and scalable framework for estimating forest structure, with greater predictive accuracy for stand density than biomass.